Lateral vibration of square plates subject to in-plane loadings - Tabarrok, B.; Fenton, R.G.; Elsaie, A.M. (Journal of sound and vibration, 1987)
The first three critical frequencies of vibration of square plates are determined by using a refined plate bending element with 18 degrees of freedom. Results are computed for different edge conditions and loading types, with the loading intensity increased from zero to the buckling load, and the variations in critical frequencies are determined in terms of the applied load intensity.